Parental perceptions of a wearable vital signs monitor for observation of newborns: in-depth interviews in three tertiary hospitals, Southwest Nigeria - John-Akinola, Yetunde Olufisayo; Ayede, Adejumoke Idowu; Adeyemi, Ayomide; Nantume, Assumpta; Olaleye, Adesewa Oluwatomisin; Akinrinoye, Olugbenga; Tongo, Olukemi Oluwatoyin; Alao, Michael Abe; Oluleye, Adenike; Sobande, Oluseye; Olayemi, Olatayo Sunday; Oketch, Bertha Akinyi; et al. (Frontiers in Digital Health, 2025)
IntroductionThe first 28 days of a newborn's life are a critical time for their survival and subsequent growth and development. Wearable devices have emerged as a potential solution for clinical monitoring, offering affordability, accessibility, and improved patient care. This study explored the acceptability, satisfaction, and perceived benefits of the neoGuard wearable vital signs monitoring device among parents/guardians of sick newborns in Nigeria.MethodsThis was a qualitative study conducted between April and December 2022 at three tertiary level health facilities in Nigeria. In-depth interviews were conducted with 17 parents/guardians whose newborns were monitored using the neoGuard technology. Participants were selected based on specific criteria, including observation of at least 2 h of use of the neoGuard technology on their newborn, and interviews were conducted in the participants’ preferred language. Interviews were moderated with a semi-structured interview guide and audio recorded. Data were transcribed, coded and analyzed thematically using NVivo software.ResultsThe majority of participants expressed positive reactions to the neoGuard device, although some initial concerns were reported. Participants appreciated the device's functionality, ease of use, and potential to detect health issues in newborns. The device did not interfere with routine care activities such as cleaning, breastfeeding, or kangaroo care. Participants expressed high levels of confidence in the device's safety and expressed satisfaction with its performance. They suggested improvements such as designing the device to be worn on the wrist instead of the forehead.ConclusionOverall, the neoGuard wearable vital signs monitor was well accepted by parents/guardians of sick newborns in Nigeria. The device's functionality, ease of use and potential to improve newborn health were positively perceived. Some suggestions for design improvements were provided. These findings highlight the importance of considering the perspectives of parents/guardians, alongside clinicians and other stakeholders, when implementing new technologies in clinical care. Further research should examine the device's clinical impact and cost-effectiveness while considering the experiences and perceptions of both healthcare providers and patients’ guardians to inform adoption into clinical practice.